post- ANALISIS EFEKTIVITAS PROGRAM PENGURANGAN POKOK PAJAK DAN PENGHAPUSAN DENDA SECARA OTOMATIS UNTUK TUNGGAKAN PAJAK PBB-P2 TAHUN 1994 HINGGA 2022 TERHADAP PENGURANGAN PIUTANG PBB-P2 DI KOTA YOGYAKARTA: EFEKTIVITAS PROGRAM PENGURANGAN POKOK PAJAK DAN PENGHAPUSAN DENDA SECARA OTOMATIS - RAFSANJANI, IHZA SAFIRA RAFSANJANI; Zulkifli, Zulkifli (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2025)
This study evaluates the effectiveness of the Automatic Principal Tax Reduction and Penalty Waiver Program on overdue Rural and Urban Land and Building Tax (PBB-P2) arrears from 1994 to 2022 in Yogyakarta City. Regulated under Mayor Decree No. 72 of 2024 and No. 356 of 2024, the program offers up to 75% principal tax reduction and automatic penalty waivers without taxpayer applications. Using a descriptive approach, data were collected through interviews with tax officers and financial reports from the Yogyakarta City Regional Financial and Asset Management Agency (BPKAD). Analysis was based on Duncan's effectiveness theory and the Minister of Home Affairs Decree No. 690.900.327 of 1996. The findings reveal that the program is ineffective, reducing PBB-P2 arrears by only IDR 15,822,801,892 (36%) against a target of IDR 44,122,193,178, below the 60% effectiveness threshold. The average monthly reduction was -1.41%, similar to the pre-program period (-1,07%). While the program meets Duncan's adaptation indicator, it fails to achieve goal attainment and integration. Key challenges include low public awareness and limited human resources among tax officers. Recommendations include intensifying socialization, increasing tax officer capacity, providing additional incentives, and conducting regular monitoring and evaluation.